Maternal and neonatal morbidity associated with higher-order of four or more repeat cesarean sections: a retrospective cohort analysis in Dubai - Cherifi, Fatima; Godara, Juhi; Hubaishi, Nawal; Mohsen, Wafa Fethi; Waheed, Seema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Cesarean delivery rates have surged globally over the past few decades, with an increasing trend of repeat cesarean sections (CS), raising significant maternal and neonatal health concerns. The risks associated with higher-order (four or more) repeat cesarean deliveries are underexplored, especially concerning outcomes like maternal hemorrhage, uterine rupture, placenta accreta spectrum (PAS), and neonatal morbidity. This study aimed to analyze maternal and neonatal morbidity in women undergoing higher-order repeat cesarean sections, comparing these with outcomes in lower-order (three or fewer) CS deliveries, to provide insights for risk mitigation and informed decision-making. Methods: A retrospective cohort study was conducted on patients who underwent repeat cesarean deliveries from January 2018 to December 2023. Data were gathered from electronic health records, focusing on key outcomes including maternal complications (e.g., blood transfusions, adhesions, ICU admissions) and neonatal complications (e.g., NICU admissions, respiratory distress). Statistical analysis was used to assess correlations and compare morbidity outcomes between groups. Results: Findings indicated significantly higher morbidity in the higher-order CS group. Elevated risks of hemorrhage, peripartum hysterectomy, organ injuries, and neonatal NICU admissions were observed. These findings highlight the need for enhanced clinical strategies and informed counselling for women with multiple prior cesarean sections. Conclusions: This study underscored the increased maternal and neonatal risks associated with four or more repeat cesarean sections. These results support the importance of careful prenatal monitoring, informed patient counselling, and targeted interventions to mitigate risks for high-order repeat cesarean deliveries.